Portfolio Optimization in the Light of Sustainability Constraint: Evidence from Indian Capital Market (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
For the past few years, it is seen that most  of the companies are facing the pressure  to provide the information regarding their  performance based on environmental, social  and governance (ESG) issues. Although there  are very limited studies which has focused on  the optimal ways to construct sustainability based portfolios. This papertries to reduce this  gap by incorporating the ESG constraint in  portfolio optimization. The objective of the  study is to construct an optimum portfolio  by using the basic Markowitz mean-variance  optimization model and the modified mean  variance model with sustainability constraint in  order to make a comparative evaluation of basic  Markowitz model and proposed mean variance  optimization model with ESG constraint  in Indian Capital Market. The study shows  that the modified mean variance model with  sustainability constraint is very much effective in  the Indian capital market rather than the basic  Markowitz optimization model.
Keywords: Portfolio optimization; Markowitz model; Sustainability-based portfolios; NLP